Blue Melanoma Simulating Blue Nevus - Sharif, Shawana; Haque, Anwar Ul; Ahmed, Aafaq (International Journal of Pathology, 2018)
Blue Nevus is a distinct melanocytic neoplastic entity. Its counterpart Blue Melanoma posesserious problems in diagnosis due to subtle nature of atypical nuclear features. A case of BlueMelanoma is presented here where several pathologists had difficulty in rendering malignantdiagnosis. However FNAC and then excisional biopsy confirmed the diagnosis